Infra Low Frequency Neurofeedback Training for Trauma Recovery: A Case Report - Kirk, Hanno W.; Dahl, Monica Geers (Frontiers in Human Neuroscience, 2022)
This paper reviews how and why ILF Neurofeedback has proven to be a parsimonious and efficient way to remediate the neuro-physiological effects of trauma. Reference is made to several large- and small-scale institutional proof of concept experimental studies each addressing a specific kind of trauma. It ends with a case report by the author (Kirk) working with an American combat veteran. It makes the argument that given its success that ILF Neurofeedback and Alpha-Theta training become accepted as part of an integrative and holistic approach for treating survivors of trauma.